2017
DOI: 10.1111/codi.13772
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for constipation: systematic review and practice recommendations

Abstract: Aim To assess the outcomes of rectal excisional procedures in adults with chronic constipation.Method Standardised methods and reporting of benefits and harms were used for all CapaCiTY reviews that closely adhered to PRISMA 2016 guidance. Main conclusions were presented as summary evidence statements with a summative Oxford Centre for Evidence-Based Medicine (2009) level.Results Forty-seven studies were identified, providing data on outcomes in 8340 patients. Average length of procedures was 44 min and length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 62 publications
0
9
0
5
Order By: Relevance
“…The presented study cohort included eleven patients, who underwent the STARR procedure before SNS implantation. Although a current systematic review showed no evidence of the STARR procedure contributing to FI on the basis of level II evidence, urge symptoms after STARR are described in 0-34%, and de novo FI in up to 9% in individual cohorts [12,18,19]. While small rectal diameter and increased pelvic floor descent in defecography predict FI after STARR, the effect of STARR on the outcome of SNS has not been studied yet [12].…”
Section: Discussionmentioning
confidence: 82%
“…The presented study cohort included eleven patients, who underwent the STARR procedure before SNS implantation. Although a current systematic review showed no evidence of the STARR procedure contributing to FI on the basis of level II evidence, urge symptoms after STARR are described in 0-34%, and de novo FI in up to 9% in individual cohorts [12,18,19]. While small rectal diameter and increased pelvic floor descent in defecography predict FI after STARR, the effect of STARR on the outcome of SNS has not been studied yet [12].…”
Section: Discussionmentioning
confidence: 82%
“…The efficacy and safety of the STARR procedure using the Contour Transtar curved cutter stapler to treat ODS in the presence of a rectocele and/or intussusception have been supported by several prospective trials, including randomized trials and meta-analyses [1, 5]. The randomized controlled trials reported in these meta-analyses did not find significant differences regarding the complication rates when the Contour Transtar was compared to STARR performed with circular staplers like PPH01 (Ethicon Endo-Surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Die Erfolgsrate liegt bei 73–80 % und die perioperativen Komplikationen bei 13–22 %. Schwerwiegende Komplikationen wie Blutung, Anastomoseninsuffizienz oder Sepsis sind selten (2 %) beschrieben 473 . Langzeitdaten zeigen einen nachlassenden funktionellen Effekt im Verlauf 474 475 .…”
Section: Chirurgische Therapie Inklusive Sakralnervenstimulationunclassified